Hubungan Dukungan Sosial dalam Pengobatan Sklerosis Multipel - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing; Romaito Nasution; Milna Sari (Pusat Riset dan Inovasi Nasional, 2024)
This meta-analysis examined the relationship between social support and medication adherence among multiple sclerosis (MS) patients through a synthesis of 47 studies (N=12,356). The findings confirmed a significant positive correlation (r=0.42, p<0.001, 95% CI [0.38, 0.46]) with substantial heterogeneity (I²=84.0%). Contrary to Cohen et al.'s (2019) finding that informational support was the strongest predictor, our moderator analyses revealed emotional support as the most robust predictor (β=0.39, p<0.001). Furthermore, this research demonstrated that the effects of social support on MS medication adherence were stronger among women (β=0.18, p=0.023) and patients with longer disease duration (β=0.24, p=0.009), extending Franqueiro et al.'s (2023) findings regarding gender differences in social support effectiveness. Family support showed the largest effect (r=0.48, p<0.001), followed by friends (r=0.40, p<0.001) and healthcare providers (r=0.35, p<0.001). Moreover, mediation modeling revealed a significant role of self-efficacy (indirect effect=0.21, 95% CI [0.17, 0.25]), expanding upon Bandura's (2018) model. Supporting Lavorgna et al.'s (2018) findings, our results confirmed that online social support proved equally effective as offline support (Q=1.87, p=0.171). These findings demonstrated robustness through sensitivity analyses and trim-and-fill procedures, confirming resilience against publication bias (adjusted r=0.39, 95% CI [0.35, 0.43]). The novelty of this research lies in its comprehensive identification of key moderators and underlying mechanisms in the social support-medication adherence relationship and the first empirical testing of an integrated mediation model incorporating social support, self-efficacy, and medication adherence in the MS context.